Pelaksanaan Kebijajakan Akreditasi Sekolah Pada Sekolah Menengah Umum (SMU) Negeri I Toho Kecamatan Toho Kabupaten Mempawah - Sikwan, Agus; Y D, Anggreini (Jurnal Pendidikan Sosiologi dan Humaniora, 2020)
This study is entitled: "Implementation of the School Accreditation Policy in the Public High School (SMU) I Toho, Toho District, Mempawah Regency". Using qualitative analysis, the results of this study indicate that the  mplementation of the school accreditation system policy implemented by the West Kalimantan Province School Accreditation Board (BAS) towards the Toho I State High School since 2005 has been going well, and has had a positive impact on the average increase passing grade results of the Final School Examination (UAS) obtained by students majoring in Social Sciences and Natural Sciences at Toho I State High School in 2017 to 2018 when compared with the average value of UAS results obtained by Toho I State High School students in 2014, despite the increase in grades the average UAS results obtained by the students were still unsatisfactory for students' parents and the school. The results also showed that the performance of the school principal as the bureaucratic apparatus of the Toho State High School I in providing administrative services to the school community was seen from the aspect of responsiveness which could be said to be good, because school residents felt there was a communication channel provided by the Toho District Education Office to convey their aspirations. In addition, the ability of the bureaucratic apparatus at the Toho District Education Office to recognize what the school community wants through direct interaction with them, causes the demands and desires of the school community to be poured by the Toho subdistrict Education Office in the form of a work program which then get a positive response from the principal of Toho I State High School to implement it.